2017
DOI: 10.5144/0256-4947.2017.357
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Arabic version of the score for allergic rhinitis tool

Abstract: BACKGROUNDAllergic rhinitis (AR) is a common inflammation of the nasal mucosa in response to allergen exposure. We translated and validated the Score for Allergic Rhinitis (SFAR) into an Arabic version so that the disease can be studied in an Arabic population.OBJECTIVESSFAR is a non-invasive self-administered tool that evaluates eight items related to AR. This study aimed to translate and culturally adapt the SFAR questionnaire into Arabic, and assess the validity, consistency, and reliability of the translat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…RSI is a self-administered questionnaire which relies on a scoring system for symptoms that evaluate the possibility of LPR and the cut-off point was set as 13 or more to suggest the possibility of LPR [5,19]. We also used an Arabic version of SFAR, a simple self-reported tool and the cut-off point was 7 [23,24]. These symptoms included: hoarseness, throat clearing, mucus in the throat, difficulty of swallowing, coughing after lying down or eating, difficulties of breathing, annoying cough, globus pharyngeus and heartburn.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RSI is a self-administered questionnaire which relies on a scoring system for symptoms that evaluate the possibility of LPR and the cut-off point was set as 13 or more to suggest the possibility of LPR [5,19]. We also used an Arabic version of SFAR, a simple self-reported tool and the cut-off point was 7 [23,24]. These symptoms included: hoarseness, throat clearing, mucus in the throat, difficulty of swallowing, coughing after lying down or eating, difficulties of breathing, annoying cough, globus pharyngeus and heartburn.…”
Section: Methodsmentioning
confidence: 99%
“…As AR and LPR have many symptoms in common resulting from irritation to the aerodigestive tract, they may have a correlation as suggested in many studies regardless of having asthma [17,18]. In this study we used a validated reflux symptom index (RSI) in Arabic [5,[19][20][21][22] to assess LPR and an Arabic version of the score for allergic rhinitis (SFAR) [23,24] to assess AR in Syria and to find if such a correlation exists.…”
Section: Introductionmentioning
confidence: 99%
“…All patients in the study were instructed to complete the Arabic version of SFAR (supplementary materials ( available here )) [ 24 ] before being admitted to the clinic. Patients were asked to complete the questionnaire precisely according to their current condition.…”
Section: Methodsmentioning
confidence: 99%
“…In adults, the prevalence of AR range from 10% to 30%, while in children it is approximately 40% [1, 5]. A study done in the Middle East reported the prevalence of AR symptoms of participants in Western Saudi Arabia as 24%, though only 4% had a prior diagnosis of AR [10]. The prevalence and characteristics of AR among Saudi adults remains undetermined.…”
Section: Introductionmentioning
confidence: 99%